PROBLEMS IN MULTICULTURAL SOCIETY: FROM LANGUAGE POLITENESS TO HATE SPEECH - Rahmadsyah Rangkuti; Andi Pratama Lubis (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2018)
Indonesia is known as a nation that has many privileges such as cultural diversity and local wisdom. Cultural diversity that includes ethnic, linguistic and religious diversity is a gift and grace from God Almighty that must be managed and well maintained by all elements of the nation. Caring for diversity and harmonization in multicultural society in the era of information technology or globalization is the biggest challenge of the day. The goal is to maintain harmony and unity in the midst of a multicultural society. In such conditions the ability and understanding of the language politeness play an important role in maintaining the harmonization of multicultural society. Based on that, this article aims to reveal that the problems that can threaten the unity and integrity of this republic are not only derived from differences of certain political and ideological attitudes, but may also originate and begin from languages impoliteness to hate speech. Applying language politeness theory proposed by Pranowo (2009) which extracted values embedded the local wisdom of the Indonesian is considered capable in anticipating hate speech actions. Thus harmonization in multicultural society in Indonesia can be well maintained.